Current practice of preconception care by primary caregivers in the Netherlands. (3rd May 2016) - van Voorst, Sabine; Plasschaert, Sophie; de Jong-Potjer, Lieke; Steegers, Eric; Denktaş, Semiha
Abstract: Objectives: Over the past decade the value of preconception care (PCC) consultations has been acknowledged. Investments have been made to promote delivery and uptake of PCC consultations in the Dutch primary care setting. We assessed current activities, perceptions and prerequisites for delivery of PCC in primary care.Methods: A questionnaire was compiled and distributed by mail or e-mail among 1682 general practitioners (GPs) and 746 midwives in the Netherlands between 2013 and 2014.Results: The questionnaire was completed by 449 GPs and 250 midwives. While GPs and midwives were frequently asked about preconception risks, explicit requests by patients for a PCC consultation were less frequent. Although caregivers gave information on preconception risk factors, only a minority recommended PCC in the form of a dedicated consultation. Such consultations occurred infrequently. Risk factor assessment varied between GPs and midwives. Respondents' perceptions of PCC consultations, however, were generally positive. A small proportion believed that PCC medicalised pregnancy, and recognised barriers in actively raising the topic of patients' pregnancy wishes. More training, staff, promotion of PCC and adequate reimbursement were prerequisites for future delivery. GPs differed in their opinion of whether they or midwives were primarily responsible for PCC consultations. Midwives, however, saw themselves as responsible for providing PCC consultations.Conclusions: Primary care is underserving prospective parents with regards to PCC consultations. Targets to increase delivery of systematic PCC are: (1) promotion during routine care; (2) increased use of tools; (3) increased collaboration among primary caregivers; (4) reduction of caregivers' negative perceptions; and (5) tailoring PCC consultations to suit women's preferences.